MANAJEMEN PROMOSI PENERIMAAN PESERTA DIDIK BARU SMA NEGERI OLAH RAGA PROVINSI RIAU - Rika Yunandar; Isjoni; Daviq Chairilsyah (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
This article reports an analysis of promotion management at SMAN Sports of Riau Province. The research entitled "Management of Promotion for New Student Admissions at SMAN Sports Riau" used a qualitative descriptive approach. The data were obtained through interviews on the sources of research information and observations observed in the institutions and the environment around the institution regarding promotion carried out by SMAN Sports Riau. Sources of data were the principal, public relations, committee that accepted new students, and teachers. Data analysis used the Analysis Interactive model of Miles and Huberman. The research outcome based on the planning of promotion in terms of the acceptance of new students at the Riau Sports Public High School has been applied well. Riau Sports Public High School in planning the promotion has planned specific management for promotion in terms of acceptance of new students. The organization of promotion in terms of the acceptance of new students at the Riau Sports Public High School has been implemented well. Organizing activities conducted were the activity for distributing the roles to all committees. The implementation of promotion in terms of the acceptance of new students at the Sports Public High School has been implemented well. It could be seen from the implementation of promotions that have been applied over the entire regencies or cities in Riau Province run well in accordance with the planning and organizing. Supervision of the promotion for new student admissions at the Sports Public High School has been applied well. The principal and the committee of new student admissions together have reviewed and classified the problems faced as long as advertizing promotion.